The Development of Quizziz-Assisted Sequence and Series Module to Increase Mathematical Understanding Ability of Senior High School Students - Miftah Ashidiqi; Asep Ikin Sugandi (IKIP Siliwangi, 2023)
Mathematical understanding is a very important aspect and the basis for students' mathematical abilities, but the fact is that mathematical understanding is still difficult for students to do. Based on the results of initial observations found problems in learning mathematics, such as students still having difficulty in (a) applying mathematical concepts, (b) students do not play an active role in the learning process, (c) teachers still use the lecture method. As a result, students do not understand the subject matter well. So from this the purpose of this study was to develop a quizziz-assisted sequence and series module to measure students' mathematical understanding abilities. The research subjects were class XII students. The research method uses R D level 1 is research and development where this research will develop and validate products without product deployment. The indicators of mathematical understanding used are: (1) identifying the concepts studied, (2) predicting a problem using the sequence concept, (3) developing the concepts studied, (4) proving understanding of a concept, (5) applying the formula to cases simple. The instruments used were tests and non-tests. The test instrument is in the form of questions and non-tests in the form of a student attitude scale questionnaire. From the results of data processing, it was obtained from ICT experts getting a score of 85.12% which was categorized as very valid, from material experts getting a score of 79.5% which was categorized as valid, the practical category got a score of 76% which was categorized as practical and the effective category averaged 68.5% which in the good category.